2006
DOI: 10.1186/1744-9081-2-34
|View full text |Cite
|
Sign up to set email alerts
|

Atypically diffuse functional connectivity between caudate nuclei and cerebral cortex in autism

Abstract: Background: Autism is a neurodevelopmental disorder affecting sociocommunicative behavior, but also sensorimotor skill learning, oculomotor control, and executive functioning. Some of these impairments may be related to abnormalities of the caudate nuclei, which have been reported for autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(111 citation statements)
references
References 110 publications
14
95
1
1
Order By: Relevance
“…The slower overall reaction time and movement times are consistent with previous work which supports the notion of basal ganglia-striatal involvement (Singh and Rivas 2004;Takarae et al 2007;Turner et al 2006). Rinehart et al (2006c) examined a number of gait parameters and reported that children and adolescents with autism display features of both basal-ganglia-striatal as well as cerebellar involvement.…”
Section: Discussionsupporting
confidence: 86%
“…The slower overall reaction time and movement times are consistent with previous work which supports the notion of basal ganglia-striatal involvement (Singh and Rivas 2004;Takarae et al 2007;Turner et al 2006). Rinehart et al (2006c) examined a number of gait parameters and reported that children and adolescents with autism display features of both basal-ganglia-striatal as well as cerebellar involvement.…”
Section: Discussionsupporting
confidence: 86%
“…Atypical static FC of sensorimotor regions has reported in previous studies (Anderson et al, 2011a;Mostofsky et al, 2009;Turner et al, 2006). Our findings suggest that despite the broad range of sensorimotor difficulties experienced by individuals with ASD (Minshew et al, 1997;Perry et al, 2007;Whyatt & Craig, 2013), atypical functioning with the SMN may be common across the autism spectrum.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 52%
“…Similarly, weaker functional connectivity has also been reported in cortical-subcortical networks; for instance, between the visual cortex and the thalamus and cerebellum (Villalobos et al, 2005), and between the superior frontal gyrus and the caudate nucleus (Turner et al, 2006). While these studies all reported functional underconnectivity in ASD in non-frontal posterior network, the findings vary across a wide variety of pairs of regions and across a large range of tasks, making it difficult to isolate a specific pattern of disturbance.…”
Section: Functional Connectivity Mri (Fcmri) Studies In Asdmentioning
confidence: 88%